Enhancing English Reading Comprehension through Gamified Digital Platforms - Sari, Anita (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study investigates the effectiveness of integrating gamification tools—specifically Quizizz, Kahoot, Pear Deck, and Nearpod—in improving English reading comprehension among first-year students at Universitas Pamulang, Indonesia. Utilizing a pre-experimental design with pretest and posttest assessments, the research measured students’ proficiency in literal, inferential, and critical comprehension aligned with the KET-Cambridge international exam format. A census sample of 27 students participated in a semester-long intervention where gamified activities were embedded into classroom instruction. Results revealed significant improvements: while 57.14% of the experimental group achieved “Outstanding” posttest scores, none remained at the “Beginning” level. Qualitative and quantitative data highlighted enhanced vocabulary acquisition, engagement, and familiarity with exam structures, supported by real-time feedback and interactive elements. The findings align with prior research on gamification’s role in fostering motivation and academic performance. This study underscores the potential of gamified tools to transform traditional language pedagogy, particularly in contexts requiring alignment with global standards. Recommendations include broader adoption of such tools in higher education and further exploration of their applicability across language skills.